Pengaruh Transfer Pricing, Capital Intensity, dan Kepemilikan Keluarga Terhadap Tax Avoidance (Studi Empiris Pada Perusahaan Consumer Non-Cyclicals Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Widianti, Reyna; Wirya Atmaja, Sri Nitta Crissiana (JURNAL PUNDI, 2024)
This research aims to determine the influence of Transfer Pricing, Capital Intensity and Family Ownership on Tax Avoidance in Non-Cyclical Consumer Sector Manufacturing Companies listed on the Indonesia Stock Exchange. The research period carried out was the 2018-2022 period. The type of research used in this research is quantitative with secondary data. Determining the sample for this research used a purposive sampling method and based on existing criteria, 14 company data was obtained and analyzed using panel data regression techniques with a fixed effect model to test the hypothesis. Hypothesis testing in this research uses multiple linear regression using Eviews version 9. The results of this research show that simultaneously transfer pricing, capital intensity and family ownership together have an effect on tax avoidance. The ability of the independent variable in the dependent variable is 33.68% while the remaining 66.32% is explained by research other than this research. The results of this research show that transfer pricing partially influences tax avoidance, while capital intensity and family ownership do not influence tax avoidance. Keywords: Transfer Pricing, Capital Intensity, Family Ownership, andTax Avoidance.